2022
DOI: 10.1002/jmri.28474
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Prognostic Factors and Molecular Subtypes of Breast Cancer With a Continuous‐Time Random‐Walk MR Diffusion Model: Using Whole Tumor Histogram Analysis

Abstract: Background The continuous‐time random‐walk (CTRW) diffusion model to evaluate breast cancer prognosis is rarely reported. Purpose To investigate the correlations between apparent diffusion coefficient (ADC) and CTRW‐specific parameters with prognostic factors and molecular subtypes of breast cancer. Study Type Retrospective. Population One hundred fifty‐seven women (median age, 50 years; range, 26–81 years) with histopathology‐confirmed breast cancer. Field Strength/Sequence Simultaneous multi‐slice readout‐se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…By calculating the characteristic parameters of ROI in the images, it evaluates the distribution of ROI grayscale intensity, provides more and more comprehensive quantitative informations, and has the advantages of simple operation, quantitative objective, and strong repeatability. To date, multiple studies available in the literature have reported that histogram analysis performs well in distinguishing between benign and malignant tumors, evaluating response to treatment, as well as predicting prognosis [22][23][24]. In this study, the histogram parameters of LL and LIP were analyzed to explore the feasibility and the value of CT images gray-scale histogram in identifying between LL and LIP.…”
Section: Discussionmentioning
confidence: 99%
“…By calculating the characteristic parameters of ROI in the images, it evaluates the distribution of ROI grayscale intensity, provides more and more comprehensive quantitative informations, and has the advantages of simple operation, quantitative objective, and strong repeatability. To date, multiple studies available in the literature have reported that histogram analysis performs well in distinguishing between benign and malignant tumors, evaluating response to treatment, as well as predicting prognosis [22][23][24]. In this study, the histogram parameters of LL and LIP were analyzed to explore the feasibility and the value of CT images gray-scale histogram in identifying between LL and LIP.…”
Section: Discussionmentioning
confidence: 99%
“…The standardized mean difference in ADC with a 95% confidence interval was used as a summary statistic for ER, PgR, and HER2 categories. A total of 52 articles [ 3 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 ] were finally reviewed and quantitatively summarized ( Fig. 1 ).…”
Section: Relationship Between Adc and Hormone Receptor Status Of Brea...mentioning
confidence: 99%
“…A forest plot of the mean differences in ADCs between ER-positive and -negative breast cancers from 44 studies [ 3 13 14 16 17 18 19 20 21 22 24 26 27 28 29 30 31 32 33 34 35 36 37 38 41 42 43 44 45 46 47 48 49 50 51 52 53 54 56 57 58 59 60 61 ] is given in Figure 2A . There was large heterogeneity among the studies (I 2 = 80%), but overall, ER-positive cancers exhibited significantly lower ADCs than ER-negative cancers ( P < 0.01).…”
Section: Relationship Between Adc and Hormone Receptor Status Of Brea...mentioning
confidence: 99%
See 1 more Smart Citation
“…4 The CTRW model has shown promising results in tumor gradings of pediatric brain tumors, 5 gastrointestinal stromal tumors, 6 and recently breast cancer tumors. 7 In the study by Ai et al, 7 the authors applied a wholetumor histogram analysis of diffusion parameters (D, α, and β) derived from a CTRW model to evaluate the relations of the diffusion parameters with some prognostic factors and molecular subtypes of breast cancer. From a total of 157 patients, histogram metrics of the CTRW parameters showed differences in expression of the molecular biomarkers (eg, ER, PR, and Ki-67) as well as the luminal and HER2-positive subtypes of breast cancers.…”
mentioning
confidence: 99%